PENGARUH MUATAN ETIKA DALAM PENGAJARAN AKUNTANSI KEUANGAN DAN PRESTASI MAHASISWA TERHADAP PERSEPSI ETIKA MAHASISWA - Dra. Endang Masitoh W, M.Si, Akt, CA, Wenie Yunika (PROSIDING, 2014)
This research aims to examine the influence of ethics content in financial accounting course and student achievement towards studentâs ethical perception. The data were collected from thequestionnaire distributed to the respondents. Random sampling were employed in this research.Sample and population are accounting students of faculty of economic UNIBA who have taken or is taking Lab Akt II (auditing) course. This research employs multiple linaer regression method using SPSS 17 to analyze the data to determine the relationship between variables both partially andsimultaneously. The result shows that ethics content in financial accounting course variable partially gives significant effect towards ethical perception, with the result of the significance t Test isless than 0.05. On the other hand, student achievement variable gives no significant effect due to the t Testresult of more than 0.05. Both variables, however, affect simultaneously studentâs ethical perception. It is proven by the result of significance F-test statistic 0.000<0.05.Keywords : Student, Accounting, Ethics, Achievement, Perception